Endocrine-Disrupting Compounds: An Overview on Their Occurrence in the Aquatic Environment and Human Exposure - Concetta Pironti (Water, 2021)
Endocrine-disrupting compounds (EDCs) as emerging contaminants have accumulated in the aquatic environment at concentration levels that have been determined to be significant to humans and animals. Several compounds belong to this family, from natural substances (hormones such as estrone, 17-estradiol, and estriol) to synthetic chemicals, especially pesticides, pharmaceuticals, and plastic-derived compounds (phthalates, bisphenol A). In this review, we discuss recent works regarding EDC occurrence in the aquatic compartment, strengths and limitations of current analytical methods used for their detection, treatment technologies for their removal from water, and the health issues that they can trigger in humans. Nowadays, many EDCs have been identified in significant amounts in different water matrices including drinking water, thus increasing the possibility of entering the food chain. Several studies correlate human exposure to high concentrations of EDCs with serious effects such as infertility, thyroid dysfunction, early puberty, endometriosis, diabetes, and obesity. Although our intention is not to explain all disorders related to EDCs exposure, this review aims to guide future research towards a deeper knowledge of EDCs’ contamination and accumulation in water, highlighting their toxicity and exposure risks to humans.